A comparison of hemodynamic metrics and intraluminal thrombus burden in a common iliac artery aneurysm. (8th September 2016) - Kelsey, Lachlan J.; Powell, Janet T.; Norman, Paul E.; Miller, Karol; Doyle, Barry J.
Abstract: Aneurysms of the common iliac artery (CIAA) are typically found in association with an abdominal aortic aneurysm (AAA). Isolated CIAAs, in the absence of an AAA, are uncommon. Similar to AAAs, CIAA may develop intraluminal thrombus (ILT). As isolated CIAAs have a contralateral common iliac artery for comparison, they provide an opportunity to study the hemodynamic mechanisms behind ILT formation. In this study, we compared a large isolated CIAA and the contralateral iliac artery using computational fluid dynamics to determine if hemodynamic metrics correlate with the location of ILT. We performed a comprehensive computational fluid dynamics study and investigated the residence time of platelets and monocytes, velocity fields, time‐averaged wall shear stress, oscillatory shear index, and endothelial cell activation potential. We then correlated these data to ILT burden determined with computed tomography. We found that high cell residence times, low time‐averaged wall shear stress, high oscillatory shear index, and high endothelial cell activation potential all correlate with regions of ILT development. Our results show agreement with previous hypotheses of thrombus formation in AAA and provide insights into the computational hemodynamics of iliac artery aneurysms. Abstract : In this study, we compared a large isolated aneurysm of the common iliac artery and the contralateral iliac artery using computational fluid dynamics to determine if hemodynamic metrics correlate with the location of ILT. We investigated the residence behavior of particles, the velocity fields, time‐averaged wall shear stress, oscillatory shear index, and endothelial cell activation potential. Our results show agreement with previous hypotheses of thrombus formation in abdominal aortic aneurysm and provide insights into the computational hemodynamics of iliac artery aneurysms.